Curricular change for social justice: Teaching science by drawing on students’ lived rural home experiences in higher education - Emmanuel Madondo, Nkosinathi (Critical Studies in Teaching and Learning, 2023)
he likely presentation of scientific knowledge as faithful copies of reality, as well as orderly activitiesfrom science textbooks,could lead novice students in the field of science to believethat the learning of scientific concepts such asaccuracy,precision,and methods such as observations, among others, may only take place in the classroom. Contrary to how scientificconcepts and methods are normally presented by means of empirical qualitative data, in this article, I argue that the abovementioned concepts and methods are likely to be encountered in  the  local  rural home environments  of  students.  Data  was  sourced  from  focus  group interviews that were conducted with second-year science students at one of the historically white and privileged institutions in South Africa. This article aims to contribute in theoretically informed ways in terms of enhancing equity of success and social justice in the field of science in  higher  education.  Social  justice  issues  were  conceptualized  through  Nancy  Fraser’s normative framework of social justice. From this understanding,an argument is put forwardthat a sociological framework of critical realism and social realism hasthe potential to draw the scientific world into the social world. From this sociological framework, it is possible to develop an understanding of students’ prior experience and to draw onit in the classroom for better educational outcomes.